2022
DOI: 10.1002/tpg2.20258
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide identification of R2R3‐MYB family genes and gene response to stress in ginger

Abstract: Ginger (Zingiber officinale Roscoe) is an important plant used worldwide for medicine and food. The R2R3‐MYB transcription factor (TF) family has essential roles in plant growth, development, and stresses resistance, and the number of genes in the family varies greatly among different types of plants. However, genome‐wide discovery of ZoMYBs and gene responses to stresses have not been reported in ginger. Therefore, genome‐wide analysis of R2R3‐MYB genes in ginger was conducted in this study. Protein phylogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The occurrence of these duplication events may result in the derivation of new gene functions [58]. In this study, we found 21 segmental-duplication and 4 tandem-duplication EfMYB gene pairs in the whole E. fulvus genome, and these quantities are relatively fewer than the MYB duplication gene pairs in S. spontaneum, Tripterygium wilfordii, and ginger, which also explains the relatively small number of EfMYB genes [59,60]. It has been reported that there are usually three types of new genes derived from gene replication events, namely, nonfunctionalization, new functionalization, and subfunctionalization genes [61].…”
Section: Discussionmentioning
confidence: 53%
“…The occurrence of these duplication events may result in the derivation of new gene functions [58]. In this study, we found 21 segmental-duplication and 4 tandem-duplication EfMYB gene pairs in the whole E. fulvus genome, and these quantities are relatively fewer than the MYB duplication gene pairs in S. spontaneum, Tripterygium wilfordii, and ginger, which also explains the relatively small number of EfMYB genes [59,60]. It has been reported that there are usually three types of new genes derived from gene replication events, namely, nonfunctionalization, new functionalization, and subfunctionalization genes [61].…”
Section: Discussionmentioning
confidence: 53%
“…In ginger exposed to Po-VOCs, the upregulation of genes annotated with the Pfam database for both the Myb-like DNA-binding domain (PF00249) and MYB-CC type transfactor LHEQLE motif (PF14379) suggested that exposure to Po-VOCs could be related to stress responses. Previously, it has been reported that ZoMYB transcription factors were upregulated in abiotically stressed ginger ( 70 ). In Po-VOC-exposed ginger plants, the upregulated genes annotated with the Pfam database for AP2 (PF00847) could be involved in priming ginger plants for resistance to abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…In this special section, Yao et al. (2022) conducted a comprehensive genome‐wide analysis of R2R3‐MYB genes in ginger, uncovering 299 potential ZoMYB genes categorized into eight groups. The analysis of gene duplication revealed 120 instances of segmental duplications in the ginger genome.…”
Section: Discovery Of Candidate Genes Associated With Stress Responsesmentioning
confidence: 99%